Pengaruh Kualitas Sistem, Kualitas Informasi Akuntansi, Kepuasan Pengguna dan Good Corporate Governance Terhadap Kinerja Karyawan (Studi Kasus: PT. BPD Bali Cabang Singaraja) - Putu Sri Arumiasih; Putu Eka Dian Marvilianti Dewi (Jurnal Akuntansi Profesi, 2021)
This study aimed at obtaining the empirical evidence on the influence of the use of quality of the system, the quality of accounting information, user satisfaction and Good Corporate Governance on company performance. This research is a causal research with a quantitative approach. The population in this study were 101 employees of PT BPD Bali Singaraja Branch. Methods of data collection using survey methods with research instruments using questionnaires. The data analysis technique uses multiple linear regression analysis with the help of the SPSS version 21.00 program. The results of this study indicated that system quality, accounting information quality, user satisfaction and good corporate governance have a positive and significant effect on employee performance, which means that if the quality of the system, the quality of accounting information, user satisfaction and Good Corporate Governance is increased, it will have an impact on improving employee performance.